Water quality and hospitalizations for gastrointestinal diseases in coastal cities: a case study in southern Brazil - Quartieri, Ewerton (2024)
The present study intends to verify the impact of bathing levels on the rate of hospitalizations for infectious enteropathies for the state of Rio Grande do Sul. Considering that it is expected that there will be an increase in the incidence of enteropathies as the condition of the primary contact water worsens, it is sought to empirically test this relation using the Regression with Discontinuity method, using data from FEPAM and the DATASUS, for the high season months, from November 2004 to December 2015. As selection rule between treaties and control, the national standard given by CONAMA will be used as a limit for the levels of thermotolerant coliforms, later testing this relation for the indication of the more rigorous limit given by the WHO. The results were inconclusive for the case using the standard applied by CONAMA, although they showed a positive impact on hospitalization rates due to enteropathies when the WHO indication was used.